A compound containing triazine structure and its application in organic electroluminescent device

By using compounds containing triazine structure as electron transport materials for OLED devices, the shortcomings of existing materials in terms of thermal stability and electron resistance are solved, and higher luminescence efficiency and longer service life are achieved.

CN116265443BActive Publication Date: 2025-02-11JIANGSU SUNERA TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111533289.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-15
Publication Date
2025-02-11
Estimated Expiration
2041-12-15

AI Technical Summary

Technical Problem

The electronic transport materials of existing OLED devices have shortcomings in terms of thermal stability and electronic resistance, resulting in poor device performance, low luminous efficiency and short service life.

Method used

A compound containing a triazine structure is used, which is connected by a bistriazine and a biphenyl structure, and the compound formed has a high glass transition temperature, good electron mobility and a deep LUMO energy level, and is used as an electron transport material.

Benefits of technology

This compound significantly improves the electron injection and transmission capabilities of OLED devices, reduces the device's driving voltage, improves luminous efficiency and working life, and enhances the film stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116265443B_ABST
    Figure CN116265443B_ABST
Patent Text Reader

Abstract

The present invention discloses a compound containing a triazine structure and its application in an organic electroluminescent device, belonging to the technical field of semiconductor materials. The structure of the compound of the present invention is shown in the general formula (1), and the compound has the characteristics of high glass transition temperature and molecular thermal stability, good electron mobility and suitable HOMO / LUMO energy level. When the compound of the present invention is used as a material for an organic electroluminescent device, the driving voltage, device efficiency and device life of the device are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor materials, in particular to a compound containing a triazine structure and application thereof in an organic electroluminescent device. Background Art

[0002] Organic light emitting diode (OLED) technology can be used to manufacture new display products as well as new lighting products. It is expected to replace existing liquid crystal displays and fluorescent lighting, and has a wide range of applications. OLED devices have a sandwich-like structure, including electrode material films and organic functional materials sandwiched between different electrode material films. Various organic functional materials are superimposed on each other according to their uses to form an OLED light-emitting device. As a current device, when voltage is applied to the electrodes at both ends of the OLED light-emitting device and the electric field acts on the positive and negative charges in the organic layer functional material film layer, the positive and negative charges are further compounded in the light-emitting layer, generating OLED electroluminescence.

[0003] Currently, OLED display technology has been applied in smart phones, tablets and other fields, and will be further expanded to large-size application fields such as TVs. However, compared with the actual product application requirements, the performance of OLED devices such as luminous efficiency and service life needs to be further improved. In order to continuously improve the performance of OLED devices, it is necessary to continuously research and innovate OLED optoelectronic functional materials to create higher performance OLED functional materials.

[0004] OLED optoelectronic functional materials used in OLED devices can be divided into two categories based on their uses, namely charge injection transport materials and luminescent materials. Furthermore, charge injection transport materials can also be divided into electron injection transport materials, electron blocking materials, hole injection transport materials and hole blocking materials. As charge transport materials, they are required to have good carrier mobility, high glass transition temperature, etc. For OLED devices, electrons are injected from the cathode and then transferred to the main material through the electron transport layer, where they recombine with holes to generate excitons. Therefore, improving the injection and transmission capabilities of the electron transport layer is conducive to reducing the device driving voltage while obtaining efficient electron-hole recombination efficiency. Therefore, the electron transport layer is very important and requires it to have efficient electron injection capability, transmission capability and high electronic durability.

[0005] For the life of the device, the heat resistance and film stability of the material are also important. Materials with low heat resistance are not only prone to decomposition during material evaporation, but also thermal decomposition caused by the heat generated by the device when the device is working, leading to material degradation. In the case of poor phase stability of the material film, the material will also undergo thin film crystallization in a short period of time, resulting in direct layer separation of the organic film layer and device degradation. Therefore, the materials used are required to have high heat resistance and good film stability.

[0006] With the significant progress of OLED devices, the performance requirements for materials are also increasing, requiring not only good material stability, but also good efficiency and life at low driving voltage. However, the current electron transport materials have insufficient heat stability and defects in the electron tolerance of the materials, resulting in phase separation or decomposition of the materials when the device is working. Summary of the invention

[0007] In view of the above problems existing in the prior art, the present invention provides a compound containing a triazine structure and its application in an organic electroluminescent device. The compound of the present invention has faster electron injection and transmission capabilities and good electron durability. When applied to an organic electroluminescent device, it can effectively reduce the operating voltage of the device and improve the luminous efficiency and service life of the device.

[0008] The technical solution of the present invention is as follows:

[0009] A compound containing a triazine structure, wherein the structure of the compound is shown in general formula (1):

[0010]

[0011] In the general formula (1), L1 represents a phenyl group, a biphenyl group or a naphthyl group;

[0012] R1, R2, R3, and R4 are independently phenyl, biphenyl, or naphthyl; the general formula (1) does not include the following structures:

[0013]

[0014] In a preferred embodiment, the structure of the compound is shown in any one of the general formulas (1-1) to (1-3):

[0015]

[0016] In general formula (1-1) to general formula (1-3), R1 to R4 have the same meanings as defined above; and the structure of the compound does not include the following structure:

[0017]

[0018] More preferably, the structure of the compound is any one of the general formulas (2-1) to (2-17):

[0019]

[0020] R1-R4 have the same meanings as defined above.

[0021] In a preferred embodiment, in the general formula (1), L1 is a phenyl group.

[0022] Preferably, in the general formula (1), R1 and R2 are independently phenyl groups. More preferably, the specific structure of the compound is any one of the following structures:

[0023]

[0024]

[0025]

[0026]

[0027]

[0028]

[0029]

[0030]

[0031]

[0032]

[0033]

[0034]

[0035]

[0036]

[0037] An organic electroluminescent device comprises a first electrode and a second electrode. A plurality of organic thin film layers are arranged between the first electrode and the second electrode of the organic electroluminescent device, and at least one organic thin film layer contains the compound containing a triazine structure.

[0038] In a preferred embodiment, the multi-layer organic thin film layer comprises an electron transport layer, and the electron transport layer contains the compound containing a triazine structure.

[0039] More preferably, the electron transport layer further comprises the compound 8-hydroxyquinoline lithium.

[0040] A display element comprises the organic electroluminescent device.

[0041] The beneficial technical effects of the present invention are:

[0042] The compound of the present invention is based on a bistriazine and biphenyl structure, and two triazine structures are connected through the ortho position of the phenyl group. The formed compound has a high glass transition temperature, electron tolerance and molecular thermal stability, as well as a suitable HOMO / LUMO energy level, and has good electron mobility. Therefore, when it is used as an electron transport material for an OLED functional layer, it can effectively improve the photoelectric performance and device life of the OLED device.

[0043] Since the triazine structure compound of the present invention can further delocalize the LUMO electron cloud distribution of the material, the electronic tolerance of the material can be improved, and the electronic stability of the material can be effectively improved. In addition, since the structure of the present invention can inhibit the π-π stacking between molecules, the electron mobility of the molecules can be significantly improved, and the driving voltage of the device can be reduced. Moreover, due to the existence of the electron-withdrawing conjugation effect of the junction of the present invention, the glass transition temperature of the material is increased, and the film stability of the material is effectively improved. Therefore, the device driving voltage can be effectively reduced and the device service life can be increased.

[0044] The compound used in the present invention is based on a bistriazine and biphenyl structure, and two triazine groups are connected to the ortho position of the phenyl group. As can be understood from the examples (described later), the compound of the above structure has a high glass transition point Tg (for example, above 120°C) and a relatively high electron mobility (greater than 6.0*E-4cm 2 / Vs), with stable film stability.

[0045] In addition, compared with the LUMO energy level of general electron transport materials (2.9-3.0 eV), this type of compound has a deeper LUMO energy level (>3.0 eV). Under the action of electric field or thermal energy, due to its strong electron-withdrawing conjugation effect, this type of compound can easily reduce and free lithium ions in lithium complexes, thereby improving the electron injection ability. Therefore, as an electron transport material, this type of compound has excellent electron transport ability and good electron injection properties, which can effectively reduce the device driving voltage, improve device efficiency, and extend the device service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is a schematic diagram of the structure of an OLED device in which the materials listed in the present invention are applied.

[0047] In the figure, 1 is a transparent substrate layer, 2 is an anode layer, 3 is a hole injection layer, 4 is a hole transport layer, 5 is an electron blocking layer, 6 is a light emitting layer, 7 is an electron transport layer, 8 is an electron injection layer, 9 is a cathode layer, and 10 is a light extraction layer. DETAILED DESCRIPTION

[0048] The technical solution of the present invention will be described in detail below in conjunction with the accompanying drawings and implementation plans.

[0049] In this application, unless otherwise specified, HOMO means the highest occupied orbital of a molecule, and LUMO means the lowest unoccupied orbital of a molecule. In addition, in the present invention, HOMO and LUMO energy levels are expressed in absolute values, and the comparison between energy levels is also a comparison of the magnitude of their absolute values. Those skilled in the art know that the greater the absolute value of an energy level, the lower the energy of the energy level.

[0050] In the accompanying drawings, the sizes of layers and regions may be exaggerated for clarity. It will also be understood that when a layer or element is referred to as being "on" another layer or substrate, the layer or element may be directly on the other layer or substrate, or there may be intervening layers. In addition, it will be understood that when a layer is referred to as being "between" two layers, the layer may be the only layer between the two layers, or there may be one or more intervening layers. The same reference numerals throughout the text represent the same elements.

[0051] In this application, when describing electrodes and organic electroluminescent devices, as well as other structures, the words "upper" and "lower" used to indicate orientation only indicate orientation in a certain state, and do not mean that the related structure can only exist in the described orientation; on the contrary, if the structure can change its position, such as being inverted, the orientation of the structure will be changed accordingly. Specifically, in the present invention, the "lower" side of the electrode refers to the side of the electrode close to the substrate during the preparation process, and the opposite side away from the substrate is the "upper" side.

[0052] Organic electroluminescent devices

[0053] In another embodiment of the present application, an organic electroluminescent device is provided, which includes a first electrode (anode), a second electrode (cathode), and a plurality of organic thin film layers located between the first electrode and the second electrode, wherein at least one organic thin film layer contains the triazine structure-containing compound.

[0054] In a preferred embodiment of the present application, the organic thin film layer comprises an electron transport layer, wherein the electron transport layer comprises the triazine structure-containing compound according to the present invention.

[0055] Preferably, in addition to the organic compound of the present invention, the electron transport layer further comprises other electron transport materials, such as Liq (see the examples for the specific chemical structure).

[0056] In a preferred embodiment of the present invention, the organic electroluminescent device according to the present invention comprises a substrate, a first electrode layer (anode layer), an organic thin film layer, a second electrode layer (cathode layer), wherein the organic thin film layer includes, but is not limited to, a light-emitting layer and a hole injection layer, a hole transport layer, an electron blocking layer, an electron transport layer, an electron blocking layer and / or an electron injection layer.

[0057] The preferred device structure of the present invention adopts the top emitting form. Preferably, the anode of the organic electroluminescent device of the present invention adopts an electrode with high reflectivity, preferably ITO / Ag / ITO; the cathode adopts a transparent electrode, preferably a mixed electrode of Mg:Ag=1:9, thereby forming a microcavity resonance effect, and the device emits light from the Mg:Ag electrode side.

[0058] In a preferred embodiment of the present invention, an organic electroluminescent device is provided, which includes a substrate, an anode, a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, an electron transport layer, an electron injection layer and a cathode layer, wherein the anode is above the substrate, the hole injection layer is above the anode, the hole transport layer is above the hole injection layer, the electron blocking layer is above the hole transport layer, the light-emitting layer is above the hole transport layer, the electron transport layer is above the light-emitting layer, the electron injection layer is above the electron transport layer, and the cathode layer is above the electron injection layer.

[0059] As the substrate of the organic electroluminescent device of the present invention, any substrate commonly used in organic electroluminescent devices can be used. Examples are transparent substrates such as glass or transparent plastic substrates; opaque substrates such as silicon substrates; flexible PI film substrates. Different substrates have different mechanical strengths, thermal stability, transparency, surface smoothness, and waterproofness. Depending on the properties of the substrate, its use direction is different. In the present invention, a transparent substrate is preferably used. The thickness of the substrate is not particularly limited.

[0060] A first electrode (anode) is formed on a substrate, and the anode material is preferably a material with a high work function so that holes are easily injected into the organic functional material layer. Non-limiting examples of anode materials include, but are not limited to, indium tin oxide (ITO), indium zinc oxide (IZO), tin oxide (SnO2), zinc oxide (ZnO), magnesium (Mg), aluminum (Al), silver (Ag), aluminum-lithium (Al-Li), calcium (Ca), magnesium-indium (Mg-In) and magnesium-silver (Mg-Ag). The first electrode can have a single-layer structure or a multilayer structure including two or more layers. For example, the anode can have a three-layer structure of ITO / Ag / ITO, but is not limited thereto. In addition, the thickness of the anode depends on the material used, typically 50-500nm, preferably 70-300nm and more preferably 100-200nm.

[0061] The hole injection layer 3 , the hole transport layer 4 and the electron blocking layer 5 may be disposed between the anode 2 and the light emitting layer 6 .

[0062] The hole injection layer structure is that the hole injection layer material is uniformly or non-uniformly dispersed in the hole transport layer, and the hole injection material can be, for example, a P dopant. The P dopant can be selected from at least one compound selected from the following: a quinone derivative, such as tetracyanoquinodimethane (TCNQ) or 2,3,5,6-tetrafluoro-tetracyano-1,4-benzoquinodimethane (F4-TCNQ); a metal oxide, such as tungsten oxide or molybdenum oxide; or a cyano-containing compound, such as the compounds P1, NDP and F4-TCNQ shown below:

[0063]

[0064] According to the present invention, P1 is preferably used as P dopant. The ratio of the hole transport layer to the P dopant used in the present invention is 99:1-70:30, preferably 99:1-85:15 and more preferably 97:3-87:13, based on mass.

[0065] The thickness of the hole injection layer of the present invention may be 1-100 nm, preferably 2-50 nm and more preferably 5-20 nm.

[0066] The material of the hole transport layer is preferably a material having a high hole mobility, which enables holes to be transferred from the anode or the hole injection layer to the light-emitting layer. The hole transport material can be a phthalocyanine derivative, a triazole derivative, a triarylmethane derivative, a triarylamine derivative, an oxazole derivative, an oxadiazole derivative, a hydrazone derivative, a stilbene derivative, a pyridoline derivative, a polysilane derivative, an imidazole derivative, a phenylenediamine derivative, an amino-substituted quilone derivative, a styrene anthracene derivative, a styrene compound such as a styrene amine derivative, a fluorene derivative, a spirofluorene derivative, a silazane derivative, an aniline copolymer, a porphyrin compound, a carbazole derivative, a polyarylalkane derivative, polyphenylene vinyl and its derivatives, polythiophene and its derivatives, poly-N-vinylcarbazole derivatives, thiophene oligomers and other conductive polymer oligomers, aromatic tertiary amine compounds, styrene amination compounds, etc. compounds, triamines, tetraamines, benzidines, propargyl diamine derivatives, p-phenylenediamine derivatives, m-phenylenediamine derivatives, 1,1'-bis(4-diarylaminophenyl)cyclohexane, 4,4'-bis(diarylamino)biphenyls, bis[4-(diarylamino)phenyl]methanes, 4,4"-bis(diarylamino)terphenyls, 4,4'"-bis(diarylamino)quaterphenyls, 4,4'-bis(diarylamino)diphenyl ethers, 4,4'-bis(diarylamino)diphenylsulfanes, bis[4-(diarylamino)phenyl]dimethylmethanes, bis[4-(diarylamino)phenyl]-bis(trifluoromethyl)methanes or 2,2-diphenylethylene compounds, etc.

[0067] The thickness of the hole transport layer of the present invention may be 5-200 nm, preferably 10-180 nm, and more preferably 20-150 nm.

[0068] The electron blocking layer requires that the triplet state (T1) energy level of the material is higher than the T1 energy level of the main material in the light-emitting layer, which can play a role in blocking the energy loss of the light-emitting layer material; the HOMO energy level of the electron blocking layer material is between the HOMO energy level of the hole transport layer material and the HOMO energy level of the main material of the light-emitting layer, which is conducive to the injection of holes from the positive electrode into the light-emitting layer. At the same time, the electron blocking layer material is required to have a high hole mobility, which is conducive to hole transport and reduces the power of the device; the LUMO energy level of the electron blocking layer material is higher than the LUMO energy level of the main material of the light-emitting layer, which plays a role in electron blocking, that is, the electron blocking layer material is required to have a wide bandgap width (Eg). The electron blocking layer materials that meet the above conditions can be triarylamine derivatives, fluorene derivatives, spirofluorene derivatives, dibenzofuran derivatives, carbazole derivatives, etc. Among them, triarylamine derivatives are preferred, such as N4,N4-bis([1,1'-biphenyl]-4-yl)-N4'-phenyl N4'-[1,1':4',1"-terphenyl]-4-yl-[1,1'-biphenyl]-4,4'-diamine; spirofluorene derivatives, such as N-([1,1'-diphenyl]-4-yl)-N-(9,9-dimethyl-9H-furan-2-yl)-9,9'-spirobifluorene-2-amine; dibenzofuran derivatives, such as N,N-di([1,1'-biphenyl]-4-yl)-3'-(dibenzo[b,d]furan-4-yl)-[1,1'-biphenyl]-4-amine, but are not limited to these.

[0069] According to the present invention, the thickness of the electron blocking layer may be 1-200 nm, preferably 5-150 nm, and more preferably 10-100 nm.

[0070] According to the present invention, the light-emitting layer is located between the first electrode and the second electrode. The material of the light-emitting layer is a material that can emit visible light by receiving holes from the hole transport region and electrons from the electron transport region respectively, and combining the received holes and electrons. The light-emitting layer may include a host material and a doping material. As the host material and guest material of the light-emitting layer of the organic electroluminescent device of the present invention, the host material may be one or a combination of two of anthracene derivatives, quinoxaline derivatives, triazine derivatives, xanthone derivatives, diphenyl ketone derivatives, carbazole derivatives, pyridine derivatives or pyrimidine derivatives. The guest material may be a pyrene derivative, a boron derivative, a chrysene derivative, a spirofluorene derivative, an iridium complex or a platinum complex.

[0071] According to the present invention, in the main material of the light-emitting layer, the ratio of the organic compound of the present invention to other main materials of the light-emitting layer is 1:9-9:1, preferably 2:8-8:2, more preferably 4:6-6:4, and most preferably 5:5. According to the present invention, the ratio of the main material to the guest material used is 99:1-70:30, preferably 99:1-85:15 and more preferably 97:3-87:13, based on mass. The thickness of the light-emitting layer of the present invention can be 5-60nm, preferably 10-50nm, and more preferably 20-45nm.

[0072] The hole blocking layer can be arranged on the light-emitting layer. The triplet state (T1) energy level of the hole blocking layer material is higher than the T1 energy level of the main material of the light-emitting layer, which can play a role in blocking the energy loss of the light-emitting layer material; the HOMO energy level of the material is lower than the HOMO energy level of the main material of the light-emitting layer, which plays a role in hole blocking. At the same time, the hole blocking layer material is required to have a high electron mobility, which is conducive to electron transmission and reduces the application power of the device; the hole blocking layer material that meets the above conditions can be triazine derivatives, azabenzene derivatives, etc. Among them, triazine derivatives are preferred; but not limited to this.

[0073] The thickness of the hole blocking layer of the present invention may be 2-200 nm, preferably 5-150 nm, and more preferably 10-100 nm, but the thickness is not limited to this range.

[0074] The electron transport layer may be disposed above the hole blocking layer. The electron transport layer material is a material that easily receives electrons from the cathode and transfers the received electrons to the light-emitting layer. The electron transport layer comprises one or more organic compounds containing a triazine structure of the present invention. Preferably, the electron transport layer is composed of the organic compound of the present invention and other electron transport layer materials. More preferably, the other electron transport layer materials are electron transport materials commonly used in the art. Most preferably, the electron transport layer is composed of the organic compound of the present invention and Liq.

[0075] The thickness of the electron transport layer of the present invention may be 10-80 nm, preferably 20-60 nm, and more preferably 25-45 nm.

[0076] In the electron transport layer of the organic electroluminescent device according to the present invention, the ratio of the organic compound of the present invention to other electron transport layer materials is 1:9-9:1, preferably 2:8-8:2, more preferably 4:6-6:4, and most preferably 5:5.

[0077] As the electron transport compound of the present invention, it is preferable to use a compound containing one or more of triazine structures.

[0078] The electron injection layer material is preferably metal Yb with a low work function, so that electrons are easily injected into the organic functional material layer. The thickness of the electron injection layer of the present invention can be 0.1-5 nm, preferably 0.5-3 nm, and more preferably 0.8-1.5 nm.

[0079] The second electrode can be a cathode, and the material for forming the cathode can be a material with a low work function, such as a metal, an alloy, a conductive compound, or a mixture thereof. Non-limiting examples of cathode materials can include lithium (Li), ytterbium (Yb), magnesium (Mg), aluminum (Al), calcium (Ca), and aluminum-lithium (Al-Li), magnesium-indium (Mg-In) and magnesium-silver (Mg-Ag). The thickness of the cathode depends on the material used, typically 5-100nm, preferably 7-50nm and more preferably 10-25nm.

[0080] Optionally, in order to improve the light extraction efficiency of the organic electroluminescent device, a light extraction layer (i.e., CPL layer) may be added on the second electrode (i.e., cathode) of the device. According to the optical absorption and refraction principle, the refractive index of the CPL layer material should be as high as possible, and the absorption coefficient should be as small as possible. Any material known in the art can be used as the CPL layer material, such as Alq3. The thickness of the CPL layer is generally 5-300 nm, preferably 20-100 nm and more preferably 40-80 nm.

[0081] Optionally, the organic electroluminescent device may further include an encapsulation structure. The encapsulation structure may be a protective structure that prevents foreign substances such as moisture and oxygen from entering the organic layer of the organic electroluminescent device. The encapsulation structure may be, for example, a can, such as a glass can or a metal can; or a film covering the entire surface of the organic layer.

[0082] Organic electroluminescent device preparation method

[0083] The present invention also relates to a method for preparing the above-mentioned organic electroluminescent device, which comprises laminating a first electrode, a multilayer organic thin film layer and a second electrode on a substrate in sequence. The multilayer organic thin film layer is formed by laminating a hole transport region, a light-emitting layer and an electron transport region from bottom to top on the first electrode in sequence, and the hole transport region is formed by laminating a hole injection layer, a hole transport layer and an electron blocking layer in sequence from bottom to top on the first electrode, and the electron transport region is formed by laminating a hole blocking layer, an electron transport layer and an electron injection layer in sequence from bottom to top on the light-emitting layer. In addition, optionally, a CPL layer can also be laminated on the second electrode to improve the light extraction efficiency of the organic electroluminescent device.

[0084] For lamination, vacuum deposition, vacuum evaporation, spin coating, casting, LB method, inkjet printing, laser printing or LITI methods may be used, but are not limited thereto. Vacuum evaporation means heating and coating a material onto a substrate in a vacuum environment.

[0085] In the present invention, the various layers are preferably formed by vacuum evaporation, wherein the layers can be formed at a temperature of about 100-500° C. and at a temperature of about 10 -8 -10 -2 Torr vacuum and approx. The vacuum evaporation is carried out at a rate of 10 -6 -10 -2 Torr, preferably 10 -5 -10 -3 Torr. The rate is about More preferably, about

[0086] In addition, it should be noted that the materials used to form each layer described in the present invention can be formed into a film alone and used as a single layer, or can be mixed with other materials to form a film and used as a single layer. It can also be a stacked structure between layers formed into films alone, a stacked structure between layers formed into films after mixing, or a stacked structure of layers formed into films alone and layers formed into films after mixing.

[0087] Display components

[0088] The present invention also relates to a display device including the above-mentioned organic electroluminescent device, in particular a flat panel display device. In a preferred embodiment, the display device may include one or more of the above-mentioned organic electroluminescent devices, and in the case of including a plurality of devices, the devices are stacked and combined laterally or longitudinally. The display device may also include at least one thin film transistor. The thin film transistor may include a gate electrode, a source electrode and a drain electrode, a gate insulating layer and an active layer, wherein one of the source electrode and the drain electrode may be electrically connected to the first electrode of the organic electroluminescent device. The active layer may include crystalline silicon, amorphous silicon, an organic semiconductor or an oxide semiconductor, but is not limited thereto.

[0089] Example

[0090] I. Compound Preparation Examples

[0091] The raw materials involved in the synthesis examples of the present invention can be purchased from the market or prepared by conventional preparation methods in the art;

[0092] Raw materials F1, F2, F3, F4, F5, F7, F8, F9, F11, F12, F13 and F14 can be purchased from the market or prepared by conventional preparation methods in the art;

[0093]

[0094] The synthesis of raw material F6 and raw material F10 is as follows:

[0095] Preparation of raw material F6:

[0096]

[0097] Under nitrogen protection, in a 500ml round-bottom flask, raw material 1 (30mmol), diboronic acid pinacol ester (33mmol, CAS: 73183-34-3), KOAC (90mmol), dioxane (200mL) were added in sequence, nitrogen was passed for 30min to replace the air, Pd(PPh3)4 (0.6mmol) was added, and heated to reflux for 12h under nitrogen protection. TCL detection of the reaction solution found that the reaction of raw material 1 was complete. After the reaction was completed, the reaction system was naturally cooled to room temperature, poured into a separatory funnel, shaken, and then allowed to stand for stratification. After separation, the aqueous phase was extracted with dichloromethane (50ml*3), the organic phases were combined, dried with anhydrous magnesium sulfate, filtered, and the filtrate was evaporated to remove dichloromethane to obtain raw material F6. LC-MS: Measured value: 512.30 ([M+H] + ); exact mass: 511.24.

[0098] Preparation of raw material F10:

[0099]

[0100] Under nitrogen protection, in a 500ml round-bottom flask, raw material 2 (30mmol), diboronic acid pinacol ester (33mmol, CAS: 73183-34-3), KOAC (90mmol), dioxane (200mL) were added in sequence, nitrogen was passed for 30min to replace the air, Pd(PPh3)4 (0.6mmol) was added, and heated to reflux for 14h under nitrogen protection. TCL detection of the reaction solution found that the reaction of raw material 2 was complete. After the reaction was completed, the reaction system was naturally cooled to room temperature, poured into a separatory funnel, shaken, and then allowed to stand for stratification. After separation, the aqueous phase was extracted with dichloromethane (50ml*3), the organic phases were combined, dried with anhydrous magnesium sulfate, filtered, and the filtrate was evaporated to remove dichloromethane to obtain raw material F6. LC-MS: Measured value: 536.35 ([M+H] + ); exact mass: 535.24.

[0101] Preparation of intermediate C1, intermediate D1, intermediate E1:

[0102]

[0103] Under nitrogen protection, in a 500ml round-bottom flask, raw material A1 (20mmol), raw material B1 (20mmol), K2CO3 (60mmol), tetrahydrofuran (150mL), water (50mL) were added in sequence, nitrogen was passed for 30min to replace the air, Pd(PPh3)4 (0.3mmol) was added, and heated under reflux for 15h under nitrogen protection. TCL detection of the reaction solution found that the raw material A1 reacted completely. After the reaction was completed, the reaction system was naturally cooled to room temperature, the solvent was removed by rotary evaporation, 120ml of dichloromethane was added to the residue to dissolve, 80ml of water was added to wash, poured into a separatory funnel and shaken, and then allowed to stand for stratification. After separation, the aqueous phase was extracted with dichloromethane (30ml*3), the organic phases were combined and dried with anhydrous magnesium sulfate, filtered, and the filtrate was evaporated to remove dichloromethane to obtain a crude product, which was purified by silica gel chromatography to obtain intermediate C1. LC-MS: Measured value: 266.87 ([M+H] + ); exact mass: 265.95.

[0104] Under nitrogen protection, in a 500ml round-bottom flask, add raw material G1 (30mmol) and ether (150mL) in sequence, cool to -78°C, pass nitrogen for 30min to replace the air, slowly add 1.6mol / L hexane solution of n-butyl lithium (40mmol), and keep at -78°C for 3h, then add trimethyl borate (40mmol), keep at -78°C for 1h, and then react the mixture at room temperature for 16h. TCL detection of the reaction solution found that the raw material G1 reacted completely. After the reaction was completed, a dilute solution of hydrochloric acid (50ml) was added to the reaction system, the organic solvent was removed by rotary evaporation, and the residue was filtered to obtain the intermediate D1 as a white solid. LC-MS: Measured value: 278.21 ([M+H] + ); exact mass: 277.10.

[0105] Under nitrogen protection, in a 500ml round-bottom flask, add intermediate C1 (30mmol), intermediate D1 (30mmol), K2CO3 (90mmol), tetrahydrofuran (200mL), water (80mL) in sequence, pass nitrogen for 30min to replace air, add Pd(PPh3)4 (0.6mmol), and heat under reflux for 15h under nitrogen protection. Take the reaction solution for TCL detection to find that the reaction of intermediate C1 is complete. After the reaction is completed, the reaction system is naturally cooled to room temperature, the solvent is removed by rotary evaporation, and the residue is dissolved in 180ml of dichloromethane, washed with 120ml of water, poured into a separatory funnel, shaken, and then allowed to stand for stratification. After separation, the aqueous phase is extracted with dichloromethane (70ml*3), the organic phases are combined, dried with anhydrous magnesium sulfate, filtered, and the filtrate is subjected to rotary evaporation to remove dichloromethane to obtain a crude product, which is purified by silica gel chromatography to obtain intermediate E1. LC-MS: Measured value: 420.18 ([M+H] +); exact mass: 419.12.

[0106] Intermediate C was prepared by a synthetic method similar to that of intermediate C1, and the raw materials A and B used were shown in Table 1;

[0107] Intermediate D was prepared by a synthetic method similar to that of intermediate D1, and the raw material G used was shown in Table 1;

[0108] Intermediate E was prepared by a synthetic method similar to that of intermediate E1, and the intermediates C and D used were shown in Table 1;

[0109] Table 1

[0110]

[0111] The mass spectrum data of intermediate D2 is LC-MS: Measured value: 354.21 ([M+H] + ); exact mass: 353.13.

[0112] The mass spectrum data of intermediate D3 is LC-MS: Measured value: 328.20 ([M+H] + ); exact mass: 327.12.

[0113] Example 1: Synthesis of Compound 4

[0114]

[0115] Under nitrogen protection, in a 250 ml round-bottom flask, intermediate E1 (10 mmol), raw material F1 (11 mmol), K2CO3 (30 mmol), tetrahydrofuran (100 mL), water (50 mL) were added in sequence, nitrogen was passed through for 30 min to replace the air, palladium acetate (0.10 mmol) and 2-dicyclohexylphosphine-2',4',6'-triisopropylbiphenyl (0.20 mmol) were added, and the mixture was heated to reflux for 18 h under nitrogen protection. The reaction solution was taken for TCL detection and found that the intermediate E1 was completely reacted. After the reaction was completed, the reaction system was naturally cooled to room temperature, the solvent was removed by rotary evaporation, 200 ml of dichloromethane was added to the residue to dissolve, 150 ml of water was added to wash, poured into a separatory funnel and shaken, and then allowed to stand for stratification. After separation, the aqueous phase was extracted with dichloromethane (80 ml * 3), the organic phases were combined and dried with anhydrous magnesium sulfate, filtered, and the filtrate was evaporated to remove dichloromethane to obtain a crude product, which was purified by silica gel column chromatography to obtain compound 4. Elemental analysis (C 50 H 34 N6) theoretical value: C, 84.07; H, 4.61; N, 11.31; test value: C, 84.04; H, 4.44; N, 11.47. LC-MS: measured value: 743.45 ([M+H] + ), exact mass: 742.28.

[0116] Example 2: Synthesis of Compound 5

[0117]

[0118] Compound 5 was prepared according to the synthesis method of compound 4 in Example 1, except that raw material F2 was used to replace F1. Elemental analysis (C 50 H 34 N6) theoretical value: C, 84.07; H, 4.61; N, 11.31; test value: C, 83.87; H, 4.52; N, 11.42. LC-MS: measured value: 743.35 ([M+H] + ), exact mass: 742.28.

[0119] Example 3: Synthesis of Compound 11

[0120]

[0121] Compound 11 was prepared according to the synthesis method of compound 4 in Example 1, except that raw material F3 was used to replace F1. Elemental analysis (C 48 H 32 N6) Calculated value: C, 83.21; H, 4.66; N, 12.13; Test value: C, 83.14; H, 4.57; N, 11.95. LC-MS: Measured value: 693.61 ([M+H] + ), exact mass: 692.27.

[0122] Example 4: Synthesis of Compound 12

[0123]

[0124] Compound 12 was prepared according to the synthesis method of compound 4 in Example 1, except that raw material F4 was used to replace F1. Elemental analysis (C 54 H 36 N6) theoretical value: C, 84.35; H, 4.72; N, 10.93; test value: C, 84.64; H, 4.45; N, 11.05. LC-MS: measured value: 769.71 ([M+H] + ), exact mass: 768.30.

[0125] Example 5: Synthesis of Compound 13

[0126]

[0127] Compound 13 was prepared according to the synthesis method of compound 4 in Example 1, except that raw material F5 was used to replace raw material F1. Elemental analysis (C54 H 36 N6) theoretical value: C, 84.35; H, 4.72; N, 10.93; test value: C, 84.53; H, 4.67; N, 10.80. LC-MS: measured value: 769.49 ([M+H] + ), exact mass: 768.30.

[0128] Example 6: Synthesis of Compound 14

[0129]

[0130] Compound 14 was prepared according to the synthesis method of compound 4 in Example 1, except that raw material F6 was used to replace raw material F1. Elemental analysis (C 54 H 36 N6) theoretical value: C, 84.35; H, 4.72; N, 10.93; test value: C, 84.11; H, 4.75; N, 10.76. LC-MS: measured value: 769.65 ([M+H] + ), exact mass: 768.30.

[0131] Example 7: Synthesis of Compound 15

[0132]

[0133] Compound 15 was prepared according to the synthesis method of compound 4 in Example 1, except that raw material F7 was used to replace raw material F1. Elemental analysis (C 52 H 34 N6) theoretical value: C, 84.07; H, 4.61; N, 11.31; test value: C, 84.17; H, 4.75; N, 11.37. LC-MS: measured value: 743.33 ([M+H] + ), exact mass: 742.28.

[0134] Example 8: Synthesis of Compound 16

[0135]

[0136] Compound 16 was prepared according to the synthesis method of compound 4 in Example 1, except that raw material F8 was used to replace raw material F1. Elemental analysis (C 52 H 34 N6) theoretical value: C, 84.07; H, 4.61; N, 11.31; test value: C, 83.96; H, 4.67; N, 11.16. LC-MS: measured value: 743.61 ([M+H] + ), exact mass: 742.28.

[0137] Example 9: Synthesis of Compound 21

[0138]

[0139] Compound 21 was prepared according to the synthesis method of compound 4 in Example 1, except that raw material F9 was used to replace raw material F1. Elemental analysis (C 56 H 36 N6) theoretical value: C, 84.82; H, 4.58; N, 10.60; test value: C, 84.72; H, 4.33; N, 10.27. LC-MS: measured value: 793.41 ([M+H] + ), exact mass: 792.30.

[0140] Example 10: Synthesis of Compound 39

[0141]

[0142] Compound 39 was prepared according to the synthetic method of compound 4 in Example 1, except that intermediate E2 was used to replace intermediate E1, and raw material F3 was used to replace raw material F1. Elemental analysis (C 54 H 36 N6) theoretical value: C, 84.35; H, 4.72; N, 10.93; test value: C, 84.67; H, 4.92; N, 11.04. LC-MS: measured value: 769.45 ([M+H] + ), exact mass: 768.30.

[0143] Example 11: Synthesis of Compound 95

[0144]

[0145] Compound 95 was prepared according to the synthetic method of compound 4 in Example 1, except that intermediate E3 was used to replace intermediate E1, and raw material F3 was used to replace raw material F1. Elemental analysis (C 52 H 34 N6) Calculated value: C, 84.07; H, 4.61; N, 11.31; Test value: C, 84.19; H, 4.67; N, 11.10. LC-MS: Measured value: 743.54 ([M+H] + ), exact mass: 742.28.

[0146] Example 12: Synthesis of Compound 167

[0147]

[0148] Compound 167 was prepared according to the synthesis method of compound 4 in Example 1, except that raw material F10 was used to replace raw material F1. Elemental analysis (C 54 H 36 N6) theoretical value: C, 84.35; H, 4.72; N, 10.93; test value: C, 84.25; H, 4.47; N, 10.76. LC-MS: measured value: 769.57 ([M+H] + ), exact mass: 768.30.

[0149] Example 13: Synthesis of Compound 260

[0150]

[0151] Compound 260 was prepared according to the synthesis method of compound 4 in Example 1, except that raw material F11 was used to replace raw material F1. Elemental analysis (C 52 H 34 N6) theoretical value: C, 84.07; H, 4.61; N, 11.31; test value: C, 83.87; H, 4.90; N, 11.16. LC-MS: measured value: 743.24 ([M+H] + ), exact mass: 742.28.

[0152] Example 14: Synthesis of Compound 268

[0153]

[0154] Compound 268 was prepared according to the synthesis method of compound 4 in Example 1, except that raw material F12 was used to replace raw material F1. Elemental analysis (C 52 H 34 N6) Calculated value: C, 84.07; H, 4.61; N, 11.31; Test value: C, 83.78; H, 4.78; N, 11.11. LC-MS: Measured value: 743.31 ([M+H] + ), exact mass: 742.28.

[0155] Example 15: Synthesis of Compound 298

[0156]

[0157] Compound 298 was prepared according to the synthesis method of compound 4 in Example 1, except that raw material F13 was used to replace raw material F1. Elemental analysis (C 52 H 34N6) theoretical value: C, 84.07; H, 4.61; N, 11.31; test value: C, 84.26; H, 4.74; N, 11.24. LC-MS: measured value: 743.43 ([M+H] + ), exact mass: 742.28.

[0158] Example 16: Synthesis of Compound 306

[0159]

[0160] Compound 306 was prepared according to the synthesis method of compound 4 in Example 1, except that raw material F14 was used to replace raw material F1. Elemental analysis (C 52 H 34 N6) theoretical value: C, 84.07; H, 4.61; N, 11.31; test value: C, 84.11; H, 4.59; N, 11.40. LC-MS: measured value: 743.75 ([M+H] + ), exact mass: 742.28.

[0161] The organic compound of the present invention can be used as an electron transport material in a light-emitting device. The HOMO / LUMO energy level, glass transition temperature Tg, decomposition temperature Td, S1 energy level, T1 energy level, evaporation temperature and electron mobility of the compound of the present invention and the comparative compound were tested, and the test results are shown in Table 2. Among them, the comparative compounds ET-1, ET-2, ET-3, ET-4, ET-5, ET-6, ET-7, ET-8, ET-9 and ET-10 have the following structures:

[0162]

[0163]

[0164] Table 2

[0165]

[0166] Note 1: The triplet energy level T1 is tested by Horiba's Fluorolog-3 series fluorescence spectrometer. The material testing condition is 2*10 -5mol / L toluene solution. The glass transition temperature Tg is measured by differential scanning calorimetry (DSC, DSC204F1 differential scanning calorimeter from NETZSCH, Germany), with a heating rate of 10°C / min. The thermal weight loss temperature Td is the temperature at which the weight loss is 1% in a nitrogen atmosphere, and is measured on a TGA-50H thermogravimetric analyzer from Shimadzu, Japan, with a nitrogen flow rate of 20mL / min. The highest occupied molecular orbital HOMO energy level is tested by an ionization energy test system (IPS3), and the test is in an atmospheric environment. The evaporation temperature is a vacuum degree of 10 -4 Pa, the temperature when the material evaporation rate is 1 angstrom / s. The electron mobility was tested by the time of flight method (TOF), and the testing equipment was CMM-250 of Japan Spectrophotometry. S1 was tested by Horiba (Fluorolog-3) fluorescence spectrometer, where the test environment of S1 was room temperature and the test environment of T1 was 77K. Eg was tested by a double-beam UV-visible spectrophotometer (Beijing Puxi General Company, model: TU-1901), LUMO = HOMO-Eg.

[0167] As can be seen from Table 2, the present invention has suitable LUMO energy level, S1 energy level and triplet energy level (T1 ≥ 2.4 eV), and the compound of the present invention has higher Tg and Td, indicating that the compound of the present invention has good film phase stability and thermal stability. In addition, the electron mobility of the compound of the present invention is significantly higher, which indicates that the compound of the present invention is more suitable for devices that need to transport electrons, such as electron transport materials in organic electroluminescent devices.

[0168] The organic compound of the present invention has relatively suitable HOMO and LUMO energy levels and triplet energy levels (T1≥2.4eV), can be used as an electron transport material for an organic electroluminescent device, and has good carrier mobility, which can effectively reduce the device driving voltage. The glass transition temperature of the material is greater than 120°C, indicating that it has good film stability and inhibits material crystallization. In addition, the material of the present invention has a higher glass transition temperature and decomposition temperature, thereby improving the thermal stability of the material during evaporation, thereby improving the working stability of the device prepared therefrom.

[0169] II. Device Preparation Example

[0170] The following describes in detail the application effect of the compound synthesized according to the present invention as an electron transport material in the device through device examples 1-16 and device comparative examples 1-10. Compared with device example 1, device examples 1-16 and device comparative examples 1-10 have the same manufacturing process of the device, and use the same substrate material and electrode material, and the film thickness of the electrode material is also consistent. The difference is that the electron transport material in the device has changed. The device stacking structure is shown in Table 3, and the performance test results of each device are shown in Table 4.

[0171] The molecular structure formula of the relevant materials is shown below:

[0172]

[0173] The structures of comparative compounds ET-1, ET-2, ET-3, ET-4, ET-5, ET-6, ET-7, ET-8, ET-9 and ET-10 are shown above.

[0174] Device Example 1

[0175] The specific preparation process is as follows:

[0176] like Figure 1 As shown, the transparent substrate layer 1 is a transparent PI film, the anode is ITO (15nm) / Ag (150nm) / ITO (15nm), and the anode layer 2 is washed, that is, alkali washing, pure water washing, drying, and then ultraviolet-ozone washing are performed in sequence to remove organic residues on the surface of the anode layer. On the anode layer 2 after the above washing, a vacuum evaporation device is used to evaporate HT-1 and P-1 with a film thickness of 10nm as a hole injection layer 3, and the mass ratio of HT-1 and P-1 is 97:3. Then, HT-1 with a thickness of 135nm is evaporated as a hole transport layer 4. Then, EB-1 with a thickness of 40nm is evaporated as an electron blocking layer 5. After the above electron blocking material is evaporated, the light-emitting layer 6 of the OLED light-emitting device is prepared, which includes H1:H2=47:47 (the mass ratio of H1 and H2 is 47:47 as the main material), GD-1 as a doping material, the doping ratio of the doping material is 6% by weight, and the thickness of the light-emitting layer is 40nm. After the above-mentioned light-emitting layer 6, the compound 4 and Liq are vacuum-deposited, the mass ratio of the compound 4 and Liq is 1:1, the film thickness is 35nm, and this layer is the electron transport layer 7. On the electron transport layer 7, a Yb layer with a film thickness of 1nm is made by a vacuum evaporation device, and this layer is the electron injection layer 8. On the electron injection layer 8, a Mg:Ag electrode layer with a film thickness of 13nm is made by a vacuum evaporation device, and the mass ratio of Mg and Ag is 1:9, and this layer is the cathode layer 9. Then, on this basis, 65nm of CPL-1 is evaporated as the light extraction layer 10.

[0177] Device Examples 2-16 and Device Comparative Examples 1-10 were prepared in a similar manner to Device Example 1, and transparent PI films were used as substrates and ITO (15nm) / Ag (150nm) / ITO (15nm) were used as anodes. The difference was that the parameters in Table 3 below were used.

[0178] Table 3

[0179]

[0180]

[0181] III. Device Testing Example

[0182] The device prepared in II was tested for driving voltage, current efficiency, CIEx, CIEy and LT95 life. Voltage, current efficiency, CIEx, and CIEy were tested using an IVL (current-voltage-luminance) test system (Suzhou Fushida Scientific Instrument Co., Ltd.) at a current density of 10 mA / cm 2 LT95 refers to the time it takes for the device brightness to decay to 95% of the initial brightness. The current density during the test is 50mA / cm 2 The life test system is the EAS-62C OLED device life tester produced by Japan System Engineering Co., Ltd. The test results are shown in Table 4 below.

[0183] Table 4

[0184]

[0185]

[0186] It can be seen from the device test data results in Table 4 above that compared with the comparative devices using ET-1, ET-2, ET-3, ET-4, ET-5, ET-6, ET-7, ET-8, ET-9 and ET-10 as electron transport layer materials, the device driving voltage prepared using the compound of the present invention as the electron transport layer material is significantly reduced, while at the same time having a longer device life, for example, its life is substantially more than 1.25 times that of the comparative devices 1-10.

[0187] The structural formulas of the comparative compounds ET-1, ET-2, ET-3, ET-4, ET-5, ET-6, ET-7, ET-8, ET-9 and ET-10 used in the comparative examples are close to those of the present invention, with only differences in the triazine and the intermediate bridging group and the triazine substituent, such as the introduction of biphenyl and naphthyl groups, the connection mode of the bridging group, and the specific structure of the bridging group. However, unexpectedly, the compounds of the present invention have achieved better technical effects as electron transport materials than the comparative compounds.

[0188] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A compound containing a triazine structure, characterized in that: The structure of the compound is shown in general formula (1): In the general formula (1), L1 represents a phenyl group, a biphenyl group or a naphthyl group; R1, R2, R3, and R4 are independently phenyl, biphenyl, or naphthyl; the general formula (1) does not include the following structures:

2. The compound according to claim 1, characterized in that The structure of the compound is shown in any one of the general formulas (1-1) to (1-3): In general formula (1-1) to general formula (1-3), R1 to R4 have the same meaning as defined in claim 1; and the structure of the compound does not include the following structure:

3. The compound according to claim 1, characterized in that The structure of the compound is any one of the general formulas (2-1) to (2-17): R1-R4 have the same meanings as defined in claim 1.

4. The compound according to claim 1, characterized in that In the general formula (1), L1 represents a phenyl group.

5. The compound according to claim 1, characterized in that In the general formula (1), R1 and R2 are each independently a phenyl group.

6. The compound according to claim 1, characterized in that The specific structure of the compound is any one of the following structures:

7. An organic electroluminescent device, comprising a first electrode and a second electrode, wherein a plurality of organic thin film layers are provided between the first electrode and the second electrode of the organic electroluminescent device, characterized in that: At least one organic thin film layer contains the triazine structure-containing compound according to any one of claims 1 to 6.

8. The organic electroluminescent device according to claim 7, characterized in that: The multi-layer organic thin film layer comprises an electron transport layer, and the electron transport layer contains the triazine structure-containing compound according to any one of claims 1 to 7.

9. The organic electroluminescent device according to claim 8, characterized in that: The electron transport layer further comprises the compound 8-hydroxyquinolate lithium.

10. A display element, characterized in that: The display element comprises the organic electroluminescent device according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Organic light emission diode device containing triazine compound and application thereof

    CN107068879A

  • Compound containing triazine and carbazole and application thereof, and organic electroluminescence device

    CN108912099A